ANALISIS PROPSEK DAN PERKEMBANGAN USAHA INDUSTRI BANDENG PRESTO DI KOTA SEMARANG - Agadhita Nila Candra; Achma Hendra Setiawan (Diponegoro Journal of Economics, 2013)
Rapid changes in the industrial sector in recent years shift the role of the agricultural sector in national and regional economic structure. This showed, the higher contribution of industrial sector in national and regional economic structures. One of the potential industries in Indonesia, particularly in Semarang is presto milkfish processing industry. Although it had a good prospect, but this industry knowed have lower production value when compared to some small industries in Semarang. One of that is caused by limited capital. Therefore the Department of Marine and Fisheries Semarang have tried to help develop the business of processed fishery by providing grant the equipment of production. This study using mixed methods analysis that is  combination of quantitative and qualitative analysis. Quantitative analysis aims to describe the profile of bussiness, determine the development of business whereas quantitative analysis aims to analyze business prospects that using the R / C ratio in presto milkfish processing industry after receivied a grant from the Department of Marine and Fisheries Semarang. The results showed that presto milkfish enterprise in Semarang has varied characteristics and cost structures so that classified into three industrial scale namely small, medium and large. According to the calculation of the R / C ratio> 1, financially presto milkfish enterprise has a good prospect and deserves to be developed. In its development, presto milkfish enterprise had increased average production, working hours, sales turnover and profits in each group on a scale: small, medium and large.